Use Markers of Short Tandem Repeats (STR) for Samples of Bone in the Forensic Diagnosis of the Human Being in the in Kerbala Governorate - Hussein Majid Mahmood1 , Yasamine Khudiar Alganimi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
STR’s analysis of DNA from bone samples plays an important role in identifying missing persons. We present a method for DNA extraction from bone samples that involve complete demineralization and digestion of the sample, followed by purification by silica binding. This method, along with the multiple STR typing approach, has also proven highly successful in recovering DNA profiles from bone samples from a wide range of contexts. These methodological steps include bone cutting and grinding, DNA extraction, Re purification in case of highly inhibited samples, quantification, amplification multiplex STR, Data Analysis of the DNA Typing and The guidelines for the preparation of personal reports. the total number of study samples reached 48, whose ages ranged between (14 to 33) years divided into 3 groups, group (1) in which (16) bone samples from the son, group (2) in which (16) blood samples from the father and group (3) It contains (16) blood samples from the mother. Conformity was carried out in the identification tests for persons in the forensic evidence laboratories of the Iraqi Ministry of the Interior, according to the protocols in the Kits used and by forensic experts.